2012
DOI: 10.1002/pbc.24274
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of pre‐irradiation chemotherapy for childhood intracranial ependymoma. Children's Cancer Group protocol 9942: A report from the Children's Oncology Group

Abstract: Children with near total resection of ependymoma may benefit from pre-irradiation chemotherapy. Patients with subtotal resection have inferior outcome despite responses to chemotherapy, and should be considered for second-look surgery prior to irradiation. Pediatr Blood Cancer 2012; 59: 1183-1189. © 2012 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
54
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 29 publications
9
54
0
5
Order By: Relevance
“…In between two surgeries, there is no defi nitive indication for chemotherapy since most of the regimens tested have not shown many responses [ 2 ]. Pre-irradiation chemotherapy may compensate for an incomplete resection as it has been shown with a recently published phase II using a standard chemotherapy regimen based on cisplatin in patients with incompletely resected; in this report, patients with incompletely resected ependymomas treated with pre-irradiation chemotherapy had similar although slightly lower EFS than those with completely resected ependymomas treated with irradiation only [ 3 ]. In addition, some anecdotal reports have shown that second surgery may be facilitated by a course or two of…”
mentioning
confidence: 61%
“…In between two surgeries, there is no defi nitive indication for chemotherapy since most of the regimens tested have not shown many responses [ 2 ]. Pre-irradiation chemotherapy may compensate for an incomplete resection as it has been shown with a recently published phase II using a standard chemotherapy regimen based on cisplatin in patients with incompletely resected; in this report, patients with incompletely resected ependymomas treated with pre-irradiation chemotherapy had similar although slightly lower EFS than those with completely resected ependymomas treated with irradiation only [ 3 ]. In addition, some anecdotal reports have shown that second surgery may be facilitated by a course or two of…”
mentioning
confidence: 61%
“…Major studies have been conducted in children using more effective agents such as etoposide, carboplatin and cisplatin 9. A cooperative group study has demonstrated, with 32 patients, a 40% complete response to preradiation chemotherapy, while 14% demonstrated progressive tumour growth 15. There was 5-year overall survival rate of 71% for all patients 9.…”
Section: Discussionmentioning
confidence: 99%
“…A taxa de resposta dos ependimomas a agentes únicos é de 11%, com menos que 5% dos casos mostrando resposta completa (Bouffet and Foreman 1999). Cisplatina mostrou ser o agente mais ativo dos quimioterápicos únicos já testados (Khan, D'Souza et al 1982;Sexauer, Khan et al 1985;Walker and Allen 1988;Goldwein, Glauser et al 1990;Grundy, Wilne et al 2007;Garvin, Selch et al 2012). Naqueles raros pacientes que respondem à quimioterapia, não há um aumento significativo da sobrevida, mesmo nos casos submetidos à quimioterapia em associação ou em adição à radioterapia (Needle, Goldwein et al 1997;Robertson, Zeltzer et al 1998;Timmermann, Kortmann et al 2000).…”
Section: Quimioterapiaunclassified
“…Naqueles raros pacientes que respondem à quimioterapia, não há um aumento significativo da sobrevida, mesmo nos casos submetidos à quimioterapia em associação ou em adição à radioterapia (Needle, Goldwein et al 1997;Robertson, Zeltzer et al 1998;Timmermann, Kortmann et al 2000). Os estudos prospectivos com vários esquemas de quimioterapia também falham em mostrar resultados efetivos (Reni, Gatta et al 2007;Zacharoulis and Moreno 2009;Garvin, Selch et al 2012;Gururangan, Fangusaro et al 2012;Wright and Gajjar 2012).…”
Section: Quimioterapiaunclassified
See 1 more Smart Citation